The political determinants of the Egyptian competition law - El-Kassas, Hassan M. Hassan (AUC Knowledge Fountain, 2016)
During the 1990s, the competition law arena witnessed a huge competition laws adaptation from developing countries creating a fertile soil for scholars and practitioners of competition law to study such a phenomena. The literature mainly corresponds to the inevitable lack of enforcement of such competition legislation within developing countries. In the scholars’ attempt to address the routes of the problem, several arguments have been formed. The most important mainstream arguments focus on two different scale arguments. The first argument focuses on the pre-enactment phase that can be called “the best model”. While the second argument focuses on the post-enactment phase which concentrates its argument on analyzing the “enforcement mechanisms”. The “best model” argument provides two different points of view. The advocates of the first point of view argue that developing countries should transplant the competition law universal norms; in other words, they should transplant Western competition legislation. On the other hand, advocates of the context theory argue that developing countries should seek the contextualization approach that harness such universal/western competition law norms to the developing countries own context. Despite the fact that both “best model” and “enforcement mechanisms” seems to be theoretically different, they are related to each other in one important aspect that seems not to be recognized by the two schools’ advocates. This important fact is the role of “political determinants” of the relevant developing country. This paper focuses on the Egyptian competition law as one of the developing countries. The paper takes a different approach than mainstream literature by emphasizing the “political determinants” within the context of a developing country due to its central and important role in determining both the “best model” to be adopted in the pre-enactment phase and on the enforcement phase as well. In support of this approach, the paper magnifies the role played by “political determinants” as the third dimension that moves everything within the competition law arena, including competition policy, legislation model, and thus enforcement mechanism. The Egyptian case reflects the fact that “political determinants” should be examined more closely as it is one of the main reasons for the enforcement problems faced by developing countries.